Leaving an emissions trading scheme:Implications for the United Kingdom and the European Union - Tol, Richard S.J. (Review of Environmental Economics and Policy, 2018)
The United Kingdom (UK) may opt to leave the European Union (EU) emissions trading system (ETS) for greenhouse gases. This policy brief examines the implications. The UK is a large importer of emission permits. Thus, meeting its climate policy targets would be much more difficult without the EU ETS, costing an additional 0.2 to 0.4 percent of gross domestic product (GDP). In addition to the increased compliance costs, the UK will face transition costs for leaving the EU ETS because a central plank of UK climate policy (i.e., permit trade) will need to be replaced on short notice. Furthermore, there may be a loss of business as the carbon trade leaves London. Moreover, as UK greenhouse gas regulation diverges from the EU, distortions at the border will also increase. The impact of a UK departure from the EU ETS on the EU would be limited if the EU accepts a weaker emissions cap. Non-EU countries such as Norway, Iceland, and Liechtenstein participate in the EU ETS, and this would appear to be the best option for the UK if it leaves the EU.